Schistura paucireticulata, a new loach from Tuirial River, Mizoram, India (Teleostei: Nemacheilidae) - Lokeshwor, Y.; Vishwanath, W.; Kosygin, L. (Zootaxa, 2013)
Schistura paucireticulata, new species, is described from the Tuirial River in Mizoram, India. It is distinguished from its congeners by a combination of characters: 8–9 brown bars on the body, bars in front of the dorsal fin divided into 2-3 small bars forming a reticulations; basicaudal bar black, dissociated; dorsal fin spotted, with 4 simple and 8½ branched rays; anal fin with 3 simple and 6 branched rays; lateral line complete; caudal fin deeply emarginated with 9+8 branched rays; well developed axillary pelvic lobe; and caudal fin with numerous black spots arranged in 3–4 bars.